Dual Structure Reinforces Interfacial Polarized MXene/PVDF-TrFE Piezoelectric Nanocomposite for Pressure Monitoring - Ao, Yong; Jin, Long; Wang, Shenglong; Lan, Bolin; Tian, Guo; Xu, Tianpei; Huang, Longchao; Wang, Zihan; Sun, Yue; Yang, Tao; Deng, Weili; Yang, Fan; et al. (Nano-Micro Letters, 2025)
The emerging interfacial polarization strategy exhibits applicative potential in piezoelectric enhancement. However, there is an ongoing effort to address the inherent limitations arising from charge bridging phenomena and stochastic interface disorder that plague the improvement of piezoelectric performance. Here, we report a dual structure reinforced MXene/PVDF-TrFE piezoelectric composite, whose piezoelectricity is enhanced under the coupling effect of interfacial polarization and structural design. Synergistically, molecular dynamics simulations, density functional theory calculations and experimental validation revealed the details of interfacial interactions, which promotes the net spontaneous polarization of PVDF-TrFE from the 0.56 to 31.41 Debye. The oriented MXene distribution and porous structure not only tripled the piezoelectric response but also achieved an eightfold increase in sensitivity within the low-pressure region, along with demonstrating cyclic stability exceeding 20,000 cycles. The properties reinforcement originating from dual structure is elucidated through the finite element simulation and experimental validation. Attributed to the excellent piezoelectric response and deep learning algorithm, the sensor can effectively recognize the signals of artery pulse and finger flexion. Finally, a 3 × 3 sensor array is fabricated to monitor the pressure distribution wirelessly. This study provides an innovative methodology for reinforcing interfacial polarized piezoelectric materials and insight into structural designs. Highlights: 1 The underlying mechanism improving piezoelectricity via interfacial polarization is elucidated through combining the experimental results, molecular dynamics simulations and density functional theory calculations. 2 The piezoelectric performance of the nanocomposite is improved based on the successful construction of dual-structure. 3 The piezoelectric sensor and array are capable of identifying human physiological signals and monitoring the distribution of pressure.